Probing the phosphatidylinositol 3‐kinase/mammalian target of rapamycin pathway in gliomas: A phase 2 study of everolimus for recurrent adult low‐grade gliomas. Issue 23 (31st July 2017) - Wahl, Michael; Chang, Susan M.; Phillips, Joanna J.; Molinaro, Annette M.; Costello, Joseph F.; Mazor, Tali; Alexandrescu, Sanda; Lupo, Janine M.; Nelson, Sarah J.; Berger, Mitchel; Prados, Michael; Taylor, Jennie W.; et al.
Abstract : BACKGROUND: Activation of the phosphatidylinositol 3‐kinase (PI3K)/mammalian target of rapamycin (mTOR) pathway is common in patients with low‐grade gliomas (LGGs), but agents that inhibit this pathway, including mTOR inhibitors, have not been studied in this population. METHODS: Fifty‐eight patients with pathologic evidence of recurrence after they had initially been diagnosed with World Health Organization (WHO) grade II gliomas were enrolled into a prospective phase 2 clinical trial and received daily everolimus (RAD001) for 1 year or until progression. Tissue at the time of enrollment was analyzed for markers of PI3K/mTOR pathway activation. Thirty‐eight patients underwent serial multiparametric magnetic resonance imaging, with the tumor volume and the perfusion metrics (the fractional blood volume [fBV] for capillary density and the transfer coefficient [Kps ] for vascular permeability) measured during treatment. The primary endpoint was progression‐free survival at 6 months (PFS‐6) in patients with WHO II disease at enrollment. RESULTS: For patients with WHO II gliomas at enrollment, the PFS‐6 rate was 84%, and this met the primary endpoint ( P  < .001 for an improvement from the historical rate of 17%). Evidence of PI3K/mTOR activation by immunohistochemistry for phosphorylated ribosomal S6 Ser240/244 (p‐S6 Ser240/244 ) was associated with worse progression‐free survival (PFS; hazard ratio [HR], 3.03; P  = .004) and overall survival (HR, 12.7; P  = .01). Tumor perfusion decreased after 6 months (median decrease in fBV, 15%; P  = .03; median decrease in Kps, 12%; P  = .09), with greater decreases associated with improved PFS (HR for each 10% fBV decrease, 0.71; P  = .01; HR for each 10% Kps decrease, 0.82; P  = .04). CONCLUSIONS: Patients with recurrent LGGs demonstrated a high degree of disease stability during treatment with everolimus. PI3K/mTOR activation, as measured by immunohistochemistry for p‐S6, was associated with a worse prognosis. Tumor vascular changes were observed that were consistent with the antiangiogenic effects of mTOR inhibitors. These results support further study of everolimus for LGGs. Cancer 2017;123:4631‐4639 . © 2017 American Cancer Society . Abstract : The inhibition of mammalian target of rapamycin with everolimus has yielded a high rate of clinical stability in a phase 2 clinical trial of patients with recurrent low‐grade gliomas. Activation of the phosphatidylinositol 3‐kinase/mammalian target of rapamycin pathway appears to be an important molecular prognostic marker of clinical outcomes.